Poultry offal meal traceability in meat quail tissues using the technique of stable carbon (13C/12C) and nitrogen ( 15N/14N) isotopes - Móri, Cleusa [UNESP]; Garcia, E. A. [UNESP]; Ducatti, C. [UNESP]; Denadai, J. C. [UNESP]; Gottmann, R. [UNESP]; Mituo, M. A.O. [UNESP] (FapUNIFESP (SciELO), 2008)
Studies on the detection of animal by-products in poultry meat are rare, and non-existent on quail meat. This study aimed at detectiong increasing levels of poultry offal meal (POM) in quail meat, using carbon (13C/ 12C) and nitrogen (15N/14N) stable isotopes technique. Sixty four on-day-old male quails derived from a commercial farm were randomly distributed into seven different groups, which were fed experimental diets containing 0, 1.5, 3.0, 4.5, 6.0, 7.5, and 15% of POM. Diets were formulated to contain equal energy, protein, and amino acid levels. Four individuals per treatment were sacrificed at 42 days of age for breast muscle (Pectoralis major), keel, and tibia collection, which were subsequently submitted to analyses. Isotopic δ13C and δ15N enrichment was observed in all analyzed tissues, with the lowest detection level of 3% dietary inclusion of poultry offal meal.
Keywords: Coturnix coturnix coturnix; Diets; Stable isotopes; Traceability